2019
DOI: 10.1111/crj.13071
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of copeptin in patients with acute pulmonary thromboembolism

Abstract: Background and Aims The aim of this study was to determine the level of copeptin, which is one of the new cardiac markers in acute pulmonary thromboembolism (PE) cases, and to determine the relationship between the severity of the disease, risk classification and hospital, first month, third month and 3‐month total mortality. Methods The study included 100 cases with PE and 60 healthy control subjects. Copeptin was measured in control group. The risk grade of the cases was determined according to the sPESI ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Copeptin is released into the blood circulation in life-threatening stress conditions. These include heart failure 11 , acute coronary syndrome 8 , sepsis 18 , pulmonary hypertension 19 , and acute PE [13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copeptin is released into the blood circulation in life-threatening stress conditions. These include heart failure 11 , acute coronary syndrome 8 , sepsis 18 , pulmonary hypertension 19 , and acute PE [13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, copeptin may show a new pathophysiological axis of PE by reflecting a systemic reaction to impaired hemodynamics due to RV dysfunction in acute PE. Some studies have reported that copeptin may be a highly significant prognostic marker in early mortality and risk stratification in patients with acute PE [13][14][15] . In this study, we investigated the copeptin Biochemical analyses Blood samples were collected from patients and the control group within a maximum of six hours after the diagnosis of acute PE to evaluate the acute phase.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Deveci and colleagues [35] found that the increase of plasma copeptin level may indicate that the patient needs further evaluation, especially since copeptin level is elevated in life-threatening conditions, such as acute myocardial infarction, shock, heart failure, pneumonia, pulmonary thromboembolism and renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Also, copeptin levels were inversely correlated both with oxygen saturation and echocardiographic indexes of right ventricle dilatation and pulmonary hypertension, the latter pointing out a role for copeptin as a prognostic biomarker of obstructive cardiogenic shock in APE. Several studies on large cohorts support this assumption by showing copeptin measurement could help stratifying the short-term risk of death after APE [55][56][57][58]. Wyzgał et al found significantly higher median copeptin levels in non-survivors than in survivors (84.6 vs. 18.7 pmol/L, n = 107), as well as in patients with complicated than with benign clinical course (53.1 vs. 18.2 pmol/L), the former being predicted by copeptin levels ≥ 18.0 pmol/L (AUC 0.811) [55].…”
Section: Critical Illness and Intensive Care Settingmentioning
confidence: 94%